Evaluation of a new recombinant antigen-based Virotech Treponema pallidum screen ELISA for diagnosis of syphilis - Busse, Clemens; Navid, Mojdeh Heidary; Strubel, Andreas; Schnitzler, Paul (Clinical laboratory, 2013)
BACKGROUND: The purpose of this study was to evaluate the diagnostic performance of the new Sekisui Virotech Treponema pallidum Screen ELISA in comparison with the currently used treponemal tests, TPPA and FTA-abs, and to compare this new ELISA to the FDA approved Phoenix Trep-Sure ELISA. - METHODS: To establish the sensitivity and specificity of the Virotech Screen, 421 serum samples from different panels of infected and noninfected patients, sera from seronegative pregnant women as well as international syphilis standard sera and panels were tested. - RESULTS: In comparison to combined TPPA/FTA-abs, Phoenix Trep-Sure and Virotech Screen demonstrated a sensitivity of 100% and a specificity of 93.9% and 98.3%, respectively. All samples of a well defined syphilis serum panel were correctly identified by the Virotech test, whereas the Phoenix test identified two Treponema negative samples as equivocal. Results of both ELISAs highly correlated with TPPA negative and positive samples. The analytical sensitivity of the Virotech Screen with international standards 05/122 and 05/132 was determined at 0.02 IU/mL and 0.03 IU/mL, respectively, and was slightly superior to the Phoenix Trep-Sure. - CONCLUSIONS: The Virotech Screen ELISA demonstrated good diagnostic sensitivity and specificity when evaluated as a screening test for syphilis among various patient populations, including samples with increased rates of false-positive nontreponemal test results. Thus, the new Virotech ELISA may be used in automatic analysers as an alternative to the manual TPPA. However, the use of a confirmatory test remains a must in order to avoid false-positive results.
Gesehen am 16.12.2020